(3GdQSGdI aj Yde GdMSGHs - (3GdfXGe GdfjSGHhQj , GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQj, fXGe GdOjf GdCYQL,J (B850 (3g` s ((3eMeO Hf bGSe Hf eMeO GdYHOdi s)
(3ChdgG (B:s
(3GdMeO ddg GdaQO HdGfO hHYO aEf jbhd GdMSGH Yde dG jcGO jSJZfi Yfg WdGH GdYdhe hGdBOGH s
(3BNQgG (B:s
(3hgh GdTF eKGd BNQ CQHYI CTjGA hSOS jYOd SHYI hfUakG GdeNQL s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3JTJed Ydi af GdgfOSI hGdeSGMI hGdLHQ hGdebGHdI HChdg hbajI HGSe edG YHO Gddg GdYHOdi jQLY JGQjNgG Edi SfI (B1239 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs